Let's fill in the missing terms and select the appropriate descriptions step-by-step for the equation provided.
Original Equation:
\[ 17u + 11 + 18u = 2u - 1 \]
Step-by-Step Analysis:
-
Combine Like Terms on the Left Side: \[ 35u + 11 = 2u - 1 \] Description: Combine like terms.
-
Subtract 2u from Both Sides: \[ 35u - 2u + 11 = -1 \] \[ 33u + 11 = -1 \] Description: Subtract 2u from both sides.
-
Subtract 11 from Both Sides: \[ 33u = -1 - 11 \] \[ 33u = -12 \] Description: Subtract 11 from both sides.
-
Divide Both Sides by 33: \[ u = \frac{-12}{33} \] Description: Divide both sides by 33.
-
Simplify the Fraction: \[ u = \frac{-4}{11} \] Description: Simplifying the fraction.
Summary of Missing Terms and Descriptions:
- Combine like terms yields \( 35u + 11 \)
- After subtracting \( 2u \), we have \( 33u + 11 = -1 \)
- After subtracting \( 11 \), we get \( 33u = -12 \)
- Then, dividing by \( 33 \) gives \( u = \frac{-12}{33} \)
- Finally, simplifying gives \( u = \frac{-4}{11} \)
Complete Missing Terms:
- \( + 11 = -1 \)
- \( - 12 \) after simplifying \( -1 - 11 \)
- \( u = \frac{-12}{33} \)
- \( 33 \) as the denominator in the division.
This results in the final simplified equation: \[ u = \frac{-4}{11} \]
Now you have all required missing terms and descriptions filled correctly.